(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
The study of the change in the road is paved with specifications of the weak clay soil when adding one or more layers of plastic clamp type (geogrid) has been subjected to a vertical load using tests to find the proportion of Endurance Alcalefori (CBR), which was used the polymeric layers labeled (geogrid) the arming of ground regular and use the experience of proportion endurance Alcalefori (CBR) to study the effect of reinforcing the durability of the soil where it was observed through experience that the use of a layer of reinforcement of the clamp plastic increases the rate (CBR) by location class and the highest rate was obtained when developing clamp plasticon – site (I), where the percentage of Californians endurance 74% as well as increases endurance Californian increasing the number of layers plastic clamp user and this tells us in reducing the thickness of the road flex layers and thereby reducing the cost of construction or stays the same fish with a significant increase in the age of the road design.